The good daughter [compact disc, unabridged] : a novel - Slaughter, Karin, 1971- (Blackstone Audio, 2017)
Twenty-eight years ago, Charlotte and Samantha Quinn's happy small-town family life was torn apart by a terrifying attack on their family home. It left their mother dead. It left their father--Pikeville's notorious defense attorney--devastated. And it left the family fractured beyond repair, consumed by secrets from that terrible night. Charlie has followed in her father's footsteps to become a lawyer herself--the ideal good daughter. But when violence comes to Pikeville again--and a shocking tragedy leaves the whole town traumatized--Charlie is plunged into a nightmare.